Production of a high-efficiency cellulase complex via β-glucosidase engineering in Penicillium oxalicum - Yao, Guangshan (Biotechnol Biofuels, 2016)
BACKGROUND: Trichoderma reesei is a widely used model cellulolytic fungus, supplying a highly effective cellulase production system. Recently, the biofuel industry discovered filamentous fungi from the Penicillium genus as a promising alternative to T. reesei. RESULTS: In our study, we present a systematic over-expression analysis of nine β-glucosidase encoding genes in the wild-type strain 114-2 of Penicillium oxalicum. We found that the over-expression of BGL1, BGL4, or BGL5 significantly enhanced both β-glucosidase activity and hydrolysis efficiency of the enzyme system on filter paper. We utilised two strategies to over-express β-glucosidase in the strain RE-10 that—although over-producing cellulase, does so at the cost of the cellulase mixture deficiency. The constitutive promoter of gene pde_02864 encoding 40S ribosomal protein S8 was used to over-express three β-glucosidases: BGL1, BGL4, and BGL5. We found that all mutants show significantly enhanced levels of β-glucosidase at transcriptional, protein, and activity levels. Furthermore, the inducible promoter from bgl2 was used to conditionally over-express the β-glucosidases BGL1 and BGL4. Surprisingly, this induced expression strategy enables significantly improved expression efficiency. The BGL1 over-expressing mutant I1-13 particularly improved the β-glucosidase activity at a factor of 65-folds, resulting in levels of up to 150 U/ml. All our BGL over-expression mutants displayed significant enhancement of cellulolytic ability on both microcrystalline cellulose and filter paper. In addition, they substantially reduced the enzyme loads in the saccharification of a natural lignocellulose material delignified corncob residue (DCCR). The mutant I4-32 with over-expression of BGL4 achieved the highest glucose yield in the saccharification of DCCR at only 25 % enzyme load compared to the parental strain RE-10. CONCLUSIONS: In summary, genetically engineering P. oxalicum to significantly improve β-glucosidase activity is a potent strategy to substantially boost the hydrolytic efficiency of the cellulase cocktail, which will ultimately lead to a considerable reduction of cost for biomass-based biofuel. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13068-016-0491-4) contains supplementary material, which is available to authorized users.